Organic photovoltaic cell with 17% efficiency and superior processability. Issue 7 (5th December 2019) - Cui, Yong; Yao, Huifeng; Hong, Ling; Zhang, Tao; Tang, Yabing; Lin, Baojun; Xian, Kaihu; Gao, Bowei; An, Cunbin; Bi, Pengqing; Ma, Wei; Hou, Jianhui
Abstract: The development of organic photoactive materials, especially the newly emerging non-fullerene electron acceptors (NFAs), has enabled rapid progress in organic photovoltaic (OPV) cells in recent years. Although the power conversion efficiencies (PCEs) of the top-performance OPV cells have surpassed 16%, the devices are usually fabricated via a spin-coating method and are not suitable for large-area production. Here, we demonstrate that the fine-modification of the flexible side chains of NFAs can yield 17% PCE for OPV cells. More crucially, as the optimal NFA has a suitable solubility and thus a desirable morphology, the high efficiencies of spin-coated devices can be maintained when using scalable blade-coating processing technology. Our results suggest that optimization of the chemical structures of the OPV materials can improve device performance. This has great significance in larger-area production technologies that provide important scientific insights for the commercialization of OPV cells.